Development of Mobile-Based Attendance Application at SMPIT Ummul Qurro' Batam Using the Agile Software Development Method - Hamdani, Dadan; Nur, Siti; Hermanto, Moch. Irwan (Media Jurnal Informatika, 2025)
The digitalization of education encourages the need for an efficient and accurate attendance system. SMPIT Ummul Qurro' Batam still uses manual methods that are time-consuming and error-prone. This study designed a mobile-based attendance application using the Agile Software Development method. Data was obtained through interviews, observations, and needs analysis with teachers, staff, and school leaders. Development is carried out through six stages: planning, implementation, testing, documentation, deployment, and maintenance. The results of black-box testing showed that the application was able to support real-time attendance and exit, user data management, and automatic recap. This research proves that the Agile Software Development method is effective in producing a simple and reliable system, which increases efficiency, accuracy, and transparency while supporting the school's digital transformation.